AES Encrypted Real-Time Video Stream and Image Transmission from ESP32-CAM - Savaştürk, Pınar; Aydın, Ömer; Dalkılıç, Gökhan (My University, 2021)
With the development of technology, the demand for security has increased. Security comes to the forefront due to the increase in data produced and transmitted in real time. In this study, improvements on the security of video data transmitted in real time are proposed. Data encrypted with AES was transferred to the local server from ESP32-Cam module. The encrypted data transferred was decrypted on the local server so the user was able to access the video. In this way, the security level of the data transmitted live between the parties has been increased. Our motivation in this study is that the number of samples proposed on real-time systems is not too much.
Keywords: ESP32-CAM; secure video transmission; encrypted image transmission; Nodejs